Capability of Dynamic Governance Aspects of Thinking Across: Case Studies in Building and Environmental Planning in Strategic Areas - Marjoni Rachman; Marsuq Marsuq (Newinera Publisher, 2020)
The purpose of this study was to determine the capability of Dynamic Governance aspects of thinking across the Building and Environmental Planning in the Kutai Timur Regency Strategic Area (RTBL KSK). This research method uses qualitative research with descriptive research type. Data collection is done by: Interview, Observation, and Documentation. Activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results of the study show aspects of thinking across the Building and Environmental Planning in the Regency Strategic Area (RTBL KSK) East Kutai show indicators that are still weak in terms of evaluation and adjustment. Adopted from the Building and Environmental Planning (RTBL) can not be separated from the concept called Urban Design (UD). Urban design is three dimensional, short term, with more emphasis on safety, aesthetics/character, and harmony with the environment. The evaluation indicators that need to be considered are land use mismatches and land-use intensity. Furthermore, the KSK RTBL is a strategic program action plan for handling the problems of settlement and infrastructure development in the field of Cipta Karya in priority areas in urban areas as an area that can contribute to minimum food security for consumption in East Kutai Regency and is directed to be developed to meet the needs of East Kutai Regency.